Hip Profile in World Elite Junior Badminton Players: Impingement and Range of Motion Data from the World Junior Badminton Championship 2018 - Kaldau, Niels Christian; Kerr, Stewart; McCaig, Steve; Hölmich, Per (The Journal of Hip Surgery, 2021)
Badminton is played with repetitive high loading to the hip with lunging and jumps. In sports like soccer there is a high prevalence of femoroacetabular impingement syndrome in youth populations which may predispose them to osteoarthritis (OA). Internal rotation deficit in the hip of football players is a predictor of hip and groin pain and differences in the range of motion (ROM) of the hip between sex and different ethnicities exist. Early hip replacements in former elite badminton players due to OA seem to be a problem. There are no published values for ROM and impingement of the hip in badminton. The purpose is to report ROM and impingement of the hip in elite junior badminton players and to report any differences between sex and ethnicities. Players at the World Junior Championship 2018 were examined for hip flexion, rotation, and impingement test. Injury history was obtained from a questionnaire. Two hundred and eighty-four players of 433 aged 16 to 18 years were examined. One hundred and forty-three players answered the questionnaire. Females demonstrated greater hip ROM than males. In the dominant side hip flexion was (137.7 degrees [ ± 9.1] vs. 132.2 degrees [ ± 11.1], p < 0.001), internal rotation range of motion or IROM (60.0 degrees [ ± 10.9] vs. 49 degrees [ ± 11.1], p < 0.001) and external rotation range of motion or EROM (57.9 degrees [ ± 9.9] vs. 54.7 degrees [ ± 8.9], 0.004). Hip flexion was higher in Asian players compared with non-Asian players (139.1 degrees [ ± 8.4] vs. 130.3 degrees [ ± 10.7], p < 0.001). One hundred (35%) players had at least one positive impingement test. A possible relationship between a positive FADIR and a decrease in hip flexion was found in the dominant hip, OR 1.06 (1.02–1.11) p = 0.005. A total of 104 previous injuries lasting over 30 days were reported with five hip-related injuries. No correlation between injury and examinations was found. Females and Asians demonstrated higher ROM in the hip than males and non-Asians. Impingement of the hip is frequent and may be related to low hip flexion.
Keywords: badminton; hip; femoroacetabular impingement; range of motion